Desarrollo del datamart de comercialización para la empresa IDETY - Mantilla Yánez, Daniel Augusto (2013)
This work pretends to describe the development of the commercial datamart for IDETY insurance company. This datamart aims to agillitate handling of informacion throught the use of a powerful and easy to use tool for end users and business analyst in IDETY.In the Introduction we find general and specific objectives of this work, as well as its scope The first chapter is the theoretical framework, which describes the methodology of Ralph Kimball for datawarehousing. In addition, we will find generalities about insurance companies and the commercial process. In capther two, we review the current situation of information gathering for commercial area in IDETY. On this base we find out a justification for developing a business intelligence project...